Entrevista com o professor Daya Thussu sobre midia e academia em tempos de pandemia - Matos, Carolina Oliveira (Revista de Comunicação Dialógica, 2021)
Professor Carolina Matos interviewed professor Daya Thussu for this special edition of the magazine, translated into Portuguese by Milene Couto.